Eastern enlargement of the European Union - Rothacher, Albrecht (Družboslovne razprave, 1998)
The accession of the East European countries to the European Union presents a challenge to both the candidate countries and the EU itself. Ten former communist countries are waiting to achieve membership in the prestigious Union. This contribution summarises and analyses three criteria set by the Council of Europe in Copenhagen (system of parliamentary democracy, success fuloperation on the Union`s free common market, adherence to and implementation of the Union`s legislation) which must be met by each of the candidates in order to attain membership.
Keywords: European Union; Evropska unija; Eastern Europe; Vzhodna Evropa; Srednja Evropa; Central Europe; družbene spremembe; politične razmere; tranzicija; integracija